URGENSI HAK KEKAYAAN INTELEKTUAL DALAM SISTEM PEREKONOMIAN GLOBAL - Sofyan Tsaori, Muhammad (Bayani, 2025)
This article discusses the urgency of Intellectual Property Rights (IPR) in the context of the global economic system. Amidst the complexity of interactions between countries, companies, and individuals in the era of globalization, IPR becomes a crucial element that not only provides legal protection but also stimulates economic growth and innovation. IPR includes copyrights, patents, and trademarks, forming the foundation of a global ecosystem that supports the exchange of knowledge and innovation worldwide. Through an analysis of its crucial role in stimulating innovation, attracting investment, and enhancing international economic competitiveness, this article reveals the significance of IPR in advancing the global economy. The research method used is analytical descriptive with literature review as the data collection technique, providing a profound overview of the contributions of IPR to innovation, technology transfer, innovation-based business models, and the increased added value of products. In the context of international business, compliance with IPR standards not only offers legal protection but also creates significant economic benefits for companies, investors, and society as a whole.